Prevalence of hookworm infection and associated factors among pregnant women attending antenatal care at governmental health centers in DEMBECHA district, north West Ethiopia, 2017 - Sewnet Wongiel Misikir; Moges Wobie; Mengistie Kassahun Tariku; Simachew Animen Bante (BMC, 2020)
Abstract Background Hookworm infection is a major public health problem in developing countries. The main way people become infected with hookworm's larva is through direct skin contact with contaminated soil when walking on barefoot. It is one of a major cause of anemia in pregnant women. The objective was to assess the prevalence and associated factors of hookworm infection among pregnant women who attended antenatal care at governmental health centers in Dembecha district, Ethiopia, 2017. Methods Institutional based cross sectional study was conducted on 306 pregnant women. Study participants were selected by systematic random sampling technique from February 1 to March 30, 2017. Data collectors and supervisors were trained. Semi-structured Amharic version questionnaire was used to collect data using face to face interview technique and stool sample was examined. Collected data were entered by using Epi data version 3.1 and exported to SPSS. The exported data was analyzed and presented by using descriptive summary statistics and tables. After bivariate logistic regression analysis, all variables with a p-value < 0.25 were entered into multivariate logistic regression and p value < 0.05 considered as significantly associated with the outcome variable. Results Prevalence of hookworm infection was 32.0%. There was a positive association of hookworm infection with living in single room [AOR =2.8; 95% CI; 1.32-5.81], living with domestic animals [AOR = 3.4; 95% CI; 1.35-8.76], monthly income ≤1500 Ethiopian birr [AOR = 3.7; 95% CI; 1.76-7.64], unavailability of latrine [AOR = 2.2; 95% CI; 1.03-4.55], habit of walking on barefoot [AOR = 4.3; 95% CI; 2.17-8.48] and not habit of hand washing before meal [AOR = 3.4; 95 CI; 1.14-10.12]. Conclusion This study showed high prevalence of hookworm infection among pregnant women in the study area. Living in single room, living with domestic animals, monthly income ≤1500 Ethiopian birr, unavailability of latrine, habit of walking on barefoot and not habit of hand washing before meal had positive association with hookworm infection. Public health measure should focus on availability latrine and separation of humans and domestic animals room to decrease prevalence of hookworm infection among pregnant women.